2023
DOI: 10.1002/advs.202303807
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitylating Enzymes in Cancer and Immunity

Jiang Ren,
Peng Yu,
Sijia Liu
et al.

Abstract: Deubiquitylating enzymes (DUBs) maintain relative homeostasis of the cellular ubiquitome by removing the post‐translational modification ubiquitin moiety from substrates. Numerous DUBs have been demonstrated specificity for cleaving a certain type of ubiquitin linkage or positions within ubiquitin chains. Moreover, several DUBs perform functions through specific protein–protein interactions in a catalytically independent manner, which further expands the versatility and complexity of DUBs’ functions. Dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 606 publications
(758 reference statements)
0
3
0
Order By: Relevance
“… 156 , 157 In the past two decades, DUBs have emerged as novel drug targets for cancer and immune disorders. 158 In the foreseen future, UME inhibitors, particularly DUB inhibitors, may also enrich the therapeutic armamentarium for CVDs. Notably, in the NF‐κB signaling, which critically regulates inflammation and cell death in multiple CVDs, stimulus‐specific polyubiquitin scaffolds provide the docking sites for key upstream signaling molecules including IKKs.…”
Section: Introductionmentioning
confidence: 99%
“… 156 , 157 In the past two decades, DUBs have emerged as novel drug targets for cancer and immune disorders. 158 In the foreseen future, UME inhibitors, particularly DUB inhibitors, may also enrich the therapeutic armamentarium for CVDs. Notably, in the NF‐κB signaling, which critically regulates inflammation and cell death in multiple CVDs, stimulus‐specific polyubiquitin scaffolds provide the docking sites for key upstream signaling molecules including IKKs.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitination is a reversible process that is accomplished by deubiquitinases (DUBs). The approximately 100 DUBs in the human body are categorized into nine families [ 8 ]: ubiquitin‐specific proteases (USPs), ovarian tumor proteases (OTUs), ubiquitin C‐terminal hydrolases (UCHs), Machado‐Joseph domain‐containing proteases (MJDs, also known as Josephins), JAMM/MPN domain‐associated Zn‐depend metalloproteases (JAMMs, also known as MPN+), the motif interacting with ubiquitin (MIU)‐containing novel DUB family (MINDYs), monocyte chemotactic protein‐induced proteins (MCPIPs), permuted papain fold peptidases of dsRNA viruses and eukaryotes (PPPDEs), and zinc finger (ZnF) containing ubiquitin peptidase 1 (ZUP1) [ 9 ]. A burgeoning volume of researches has demonstrated that dysregulation of the balance between ubiquitination and deubiquitination can lead to a wide variety of adverse consequences [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitination is a dynamic and reversible process, with deubiquitinating enzymes (DUBs) able to reverse the ubiquitination of proteins ( 51 ). This process, known as deubiquitination, is essential for maintaining the balance and regulation of protein ubiquitination within the cell, impacting various cellular processes and homeostasis ( 52 , 53 ).…”
Section: Introductionmentioning
confidence: 99%